The landscape of acid sphingomyelinase deficiency in a new therapeutic era: insights from experts in the Gulf region - Moeenaldeen AlSayed; Fatma Al-Jasmi; Tawfeg Ben Omran; Fathiya Al-Murshedi; Rawda Sunbul; Nadia Al-Hashmi; Talal Al-Enazi (Journal of Biochemical and Clinical Genetics)
Acid sphingomyelinase deficiency (ASMD) is an autosomal-recessive progressive multiorgan metabolic disorder due to pathogenic variants in the sphingomyelin phosphodiesterase 1 gene. It can lead to death in early childhood in its most severe form. According to previous registries, the birth prevalence of ASMD is nearly 0.4-0.6 per 100,000 live births. The diagnosis of ASMD is usually delayed or missed due to the wide variability of clinical manifestations of the disease. Until recently, the management of ASMD patients was based on symptomatic treatments and supportive care; however, the introduction of enzyme replacement therapy (ERT) has revolutionized the management landscape of ASMD. ERT with a recombinant human Acid Sphingomyelinase Enzyme administered intravenously demonstrated a significant improvement in the non-neuronopathic type of ASMD in phase 2/3 trials. In June 2022, the European Medical Agency granted the ERT, olipudase alfa, marketing authorization. The prevalence of inherited metabolic disorders, including lysosomal storage diseases, is relatively higher in the Arab world than in the rest of the world due to the high consanguinity rate. In this study, we aim to review the current landscape of ASMD in the Gulf Cooperation Council countries and gather insights from experts regarding the roadmap to diagnosis, prevalence, and management approaches of ASMD in the region. [JBCGenetics 2023; 6(1.000): 41-56]